Self-generated diffusioosmotic flows from calcium carbonate micropumps - McDermott, Joseph J (Langmuir : the ACS journal of surfaces and colloids, 2012)
Calcium carbonate particles, ubiquitous in nature and found extensively in geological formations, behave as micropumps in an unsaturated aqueous solution. The mechanism causing this pumping is diffusioosmosis, which drives flows along charged surfaces. Our calcium carbonate microparticles, roughly ∼10 μm in size, self-generate ionic gradients as they dissolve in water to produce Ca(2+), HCO(3)(-), and OH(-) ions that migrate into the bulk. Because of the different diffusion coefficients of these ions, spontaneous electric fields of roughly 1-10 V/cm arise in order to maintain electroneutrality in the solution. This electric field drives the diffusiophoresis of charged tracers (both positive and negative) as well as diffusioosmotic flows along charged substrates. Here we show experimentally how the directionality and speed of the tracers can be engineered by manipulating the tracer zeta potential, the salt gradients, and the substrate zeta potential. Furthermore, because the salt gradients are self-generated, here by the dissolution of solid calcium carbonate microparticles another manipulated variable is the placement of these particles. Importantly, we find that the zeta potentials on surfaces vary with both time and location because of the adsorption or desorption of Ca(2+) ions; this change affects the flows significantly